IMPRESI POLITIK HUKUM NASIONAL BERLANDASKAN PANCASILA TERHADAP SISTEM PERUNDANG-UNDANGAN NASIONAL - Maheru Fata, dan Muhammad Zain, Azis Nur Arifin (GEMA, 2015)
Pancasila as legal ideals or rechtsidee has a meaning that is viewed Pancasila from the perspective of law, Pancasila as the basis and purpose of each law. Pancasila is the source of the material the material that determines the highest payload in the formation of law and as a philosophical milestones test of constitutional norms law. characteristics on politics of national law are political of law based on Pancasila. Based on various opinions say that the politics of national law is policy that will, want, and have been taken by the Government must be based on the values contained in the Indonesiaâs People from Pancasila. While the characteristics on the system of national legislation based on hierarchical systems or in sciences attempt to use the theory proposed by Hans Kelsen, best known for the theory of Stufentbau des Recht. According to Satjipto Rahardjo, law is loaded with political colors or rather that the law should be viewed as the result of a political process (law as a product of plotical process). Itâs also, political subsystem has a higher level from determination subsystem law, because the law is the result or the crystallization from the political will which of interacting and competing. So, in this case politic of law is politics of the national law are essentially based on Pancasila has authoritarian influence against patterns or characteristics of the system of legislation in the country of Indonesia.